Management information systems : managing the digital firm - Laudon, Kenneth C.; Laudon, Jane P. (Boston : Prentice Hall, 2012)
Management Information Systems provides comprehensive and integrative coverage of essential new technologies, information system applications, and their impact on business models and managerial decision making in an exciting and interactive manner. The twelfth edition focuses on the major changes that have been made in information technology over the past two years, and includes new opening, closing, and Interactive Session cases
Part one: Organizations, Management, and the Network enterprse -- Part two: Information technology infrastructure -- Part three: Key system application for he digital age -- Part four: Building and managing systems
Includes bibliographic references and index.
Keywords: INFORMATION RESOURCES MANAGEMENT; MANAGEMENT INFORMATION SYSTEMS